Relationships of dermatologic symptoms and quality of life in patients with psoriatic arthritis: analysis of two tofacitinib phase III studies - Taylor, P; Bushmakin, AG; Cappelleri, JC; Young, P; Germino, R; Merola, JF; Yosipovitch, G (Taylor and Francis, 2022)
Objectives Evaluate relationships between changes in dermatologic assessments and quality of life (QoL) measures; quantify dermatologic symptom severity impacts on QoL in patients with psoriatic arthritis (PsA) treated with tofacitinib.